Effects of topological disorder on phase separation and local order in a-si1-xgex. alloys - Tzoumanekas, Christos; Kelires, Pantelis C. (My University, 1999)
Monte Carlo simulations show that the inherent tendency for decomposition of the Si-Ge solid mixture is totally suppressed in the amorphous phase. Yet, the distribution of Si and Ge atoms in the network is not random as in the crystal, but there is a strong tendency of homopolar bonds to cluster locally, even at high temperatures. We show that the disorder potential of the amorphous network prevents the percolation of these clusters in segregated regions under thermodynamic equilibrium. However, these homopolar clusters might act as precursors of metastable decomposed regions observed in crystallization processes.
Keywords: Alloys; Crystallization